2013
DOI: 10.1123/japa.21.2.119
|View full text |Cite
|
Sign up to set email alerts
|

Does Habitual Physical Activity Prevent Insomnia? A Cross-Sectional and Longitudinal Study of Elderly Japanese

Abstract: Few epidemiological studies have examined the potential protective effects of physical activity on insomnia. The authors thus evaluated the association between physical activity and insomnia in a large population-based study in Shizuoka, Japan. Individual data were obtained from participants in an ongoing cohort study. A total of 14,001 older residents who completed questionnaires were followed for 3 yr. Of these, 10,211 and 3,697 participants were eligible for the cross-sectional and longitudinal analyses, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
3
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 29 publications
4
38
3
2
Order By: Relevance
“…This was similar to a previous research conducted in Japan in which habitual physical activity was related to lower prevalence of insomnia among the elderly [23]. Also, the present study revealed that regularly practicing hobbies was associated with a lower risk for insomnia; this was consistent with the results of a previous study conducted by Reid et al.…”
Section: Discussionsupporting
confidence: 95%
“…This was similar to a previous research conducted in Japan in which habitual physical activity was related to lower prevalence of insomnia among the elderly [23]. Also, the present study revealed that regularly practicing hobbies was associated with a lower risk for insomnia; this was consistent with the results of a previous study conducted by Reid et al.…”
Section: Discussionsupporting
confidence: 95%
“…Although there were no significant associations between any type of PA and incident short sleep duration in either middle-aged or older adults, there was a clear age difference in the association between PA intensity and incident insufficient sleep: in middle-aged adults, higher intensities of PA more effectively prevented incident insufficient sleep, but in older adults, MLPA was more effective for preventing incident insufficient sleep. This study supports the few studies that have confirmed the prospective association between PA and risk of sleep problems 32,33 and adds new information on the benefits of three types of PA for improving sleep based on age.…”
Section: Discussionsupporting
confidence: 84%
“…Four studies examined physical activity with mixed findings (see discussion) 20, 21, 24, 30 . These studies also examined demographic and other psychosocial factors: African-American race (compared to white race) 27 , previous manual occupation 24, 31 , widowhood 19, 26 , and lower economic status 25 predicted incident insomnia symptoms; recent life events predicted hypersomnia but not insomnia in one study 23 .…”
Section: Resultsmentioning
confidence: 99%